2015
DOI: 10.1016/j.compositesa.2015.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Compressive failure of hybrid multidirectional fibre-reinforced composites

Abstract: Hybridisation of multidirectional carbon fibre-reinforced composites as a means of improving the compressive performance is studied. The aim was to thoroughly investigate how hybridisation influenced the laminate behaviour under different compression conditions and thus understand the "hybrid effect". The compressive performance of two monolithic carbon fibre/epoxy systems were compared with their respective hybrids by keeping the same layup throughout but replacing the angle plies in one case or the orthogona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…In separate studies, Tsampas et al [ 9 ] evaluated the effect of monolithic and hybrid multidirectional composites laminates on compressive performance. Through the fractography analysis, the studies showed that the hybridization via multidirectional laminates was greatly influenced by the compressive performance by showing the delamination and interlaminar fracture at the hybrid interface which was more detrimental than that at the monolithic interface [ 121 ].…”
Section: Failure Mechanism Of Natural Fiber Hybrid Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…In separate studies, Tsampas et al [ 9 ] evaluated the effect of monolithic and hybrid multidirectional composites laminates on compressive performance. Through the fractography analysis, the studies showed that the hybridization via multidirectional laminates was greatly influenced by the compressive performance by showing the delamination and interlaminar fracture at the hybrid interface which was more detrimental than that at the monolithic interface [ 121 ].…”
Section: Failure Mechanism Of Natural Fiber Hybrid Compositesmentioning
confidence: 99%
“…Hybridization offers new opportunities to broaden the function of the composite materials, particularly in advanced applications by improving the toughness or impact resistance [ 2 , 9 ]. Hybrid composites also provide more design freedom compared to non-hybrid composites, which leads to a synergetic effect not possessed by any one material alone.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical models employing cohesive elements were able to accurately capture this delamination mode observed in the experiments and were shown to give excellent correlation with the ultimate strength. Future work will focus on incorporating damage models capable of modelling transverse matrix cracking which has been shown to be an important damage mechanism especially in compression [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this phenomenon has stimulated the attention of many researchers to develop sustainable, active packaging material [ 9 ]. Therefore, the design of the packaging should consider not only shelf-life, cost, and protection, but also user-friendliness and environmental sustainability [ 10 ].…”
Section: Introductionmentioning
confidence: 99%